2016
DOI: 10.1021/acs.est.5b06312
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Wave Effects on Oxygen, Nutrients, and Phytoplankton Can Alter Global Warming Potential of Gases Emitted from a Small Shallow Lake

Abstract: Increasing air temperatures may result in stronger lake stratification, potentially altering nutrient and biogenic gas cycling. We assessed the impact of climate forcing by comparing the influence of stratification on oxygen, nutrients, and global-warming potential (GWP) of greenhouse gases (the sum of CH4, CO2, and N2O in CO2 equivalents) emitted from a shallow productive lake during an average versus a heat-wave year. Strong stratification during the heat wave was accompanied by an algal bloom and chemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 75 publications
(103 reference statements)
4
42
1
Order By: Relevance
“…High temperatures amplified CH 4 emissions (Sepulveda‐Jauregui et al., ), which led to markedly higher amounts of CH 4 stored and emitted from the basins in the hotter summer of 2014 with a clear correlation between CH 4 emissions and temperature. Similar responses to regional temperature have been shown in ponds, in small shallow, and medium‐sized lakes (Bartosiewicz, Laurion, & Macintyre, ; Bartosiewicz et al., ; Encinas Fernández et al., ; Liikanen, Huttunen, Valli, & Martikainen, ; Miettinen et al., ; Natchimuthu et al., ; Room et al., ) and in enclosure experiments (Audet et al., ; Yvon‐Durocher et al., ), suggesting that in predicted warming scenarios, an increase in carbon greenhouse gas emissions can be expected in lake ecosystems regardless of DOC inputs and their biogeochemical effects in the water column (e.g., in stratification, temperature regimes, pH, microbial metabolism and CO 2 dynamics).…”
Section: Discussionsupporting
confidence: 63%
“…High temperatures amplified CH 4 emissions (Sepulveda‐Jauregui et al., ), which led to markedly higher amounts of CH 4 stored and emitted from the basins in the hotter summer of 2014 with a clear correlation between CH 4 emissions and temperature. Similar responses to regional temperature have been shown in ponds, in small shallow, and medium‐sized lakes (Bartosiewicz, Laurion, & Macintyre, ; Bartosiewicz et al., ; Encinas Fernández et al., ; Liikanen, Huttunen, Valli, & Martikainen, ; Miettinen et al., ; Natchimuthu et al., ; Room et al., ) and in enclosure experiments (Audet et al., ; Yvon‐Durocher et al., ), suggesting that in predicted warming scenarios, an increase in carbon greenhouse gas emissions can be expected in lake ecosystems regardless of DOC inputs and their biogeochemical effects in the water column (e.g., in stratification, temperature regimes, pH, microbial metabolism and CO 2 dynamics).…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, HWs might alter CH 4 emission pathways as was observed in a Canadian shallow lake where the dominant pathway of CH 4 emission shifted from ebullition to diffusion during a summer HW (Bartosiewicz et al, 2016). HWs can promote water stratification in lakes (Jankowski et al, 2006;Jeppesen, Sondergaard, Lauridsen, Liboriussen, et al, 2012) and a study of a Canadian shallow lake found that GHGs produced in the sediment were trapped in the colder water of the hypolimnion (Bartosiewicz et al, 2016). N 2 O and CH 4 fluxes might be affected by diel dynamics in light, pH (related to changes in primary production) and temperature (K€ aki, Ojala, & Kankaala, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…"0" means that the HW 1 treatment did not differ significantly from the HW 2 treatment, that is, the effect of the HW did not differ from the effect of the ambient summer temperature (see "Materials and methods" and , 2014;Michaletz, Cheng, Kerkhoff, & Enquist, 2014) and for GHG processes in shallow lakes (Bartosiewicz et al, 2016;Davidson et al, 2015). It might be at least partially explained by the effect of changes in biotic interactions related to warming overriding the direct metabolism-related temperature effect on GHGs, at least for a moderate increase in temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations